Brand positioning : connecting marketing strategy and communications - Kostelijk, Erik; Alsem, K. J. (New York : Routledge, 2020)
'Brand Positioning is an English translation of an exceptionally well-renowned Dutch textbook, which provides a practical approach to analysing, defining and developing a brand's positioning and strategy. Divided into three key parts, the book works step-by-step through the creation of an effective marketing strategy, combining an academic approach with the strategic and operational guidelines, tools and techniques required. Unlike other textbooks, it has a unique focus on the relationship between branding, marketing and communications, exploring brand values, brand identity, brand image, and analysing how these can be transformed into a successful positioning strategy, using international case studies, examples and practical exercises. This textbook will be core reading for advanced undergraduate and postgraduate students of marketing strategy, branding, marketing communications and consumer behaviour. It will also be of great value to marketing and communications professionals looking to develop and maintain their company's brand. Online resources to aid leaning include an instructor's manual, test bank with case material and multiple-choice questions, and PowerPoint slides'--
Includes bibliographical references and index.
Keywords: Branding (Marketing).; Strategic planning